Opposition to Jehovah's Witnesses in the United States Through the Twentieth Century - Melton, J. Gordon (The journal of CESNUR, 2021)
The Jehovah's Witnesses have emerged in the United States as one of the very few denominations that have attracted as many as a million members, a status that came only after battling back from both social discrimination and government persecution over some of its unpopular beliefs. In 1918, the president and several of his fellow leaders of the precursor Watch Tower Bible and Tract Society were convicted under the Espionage Act for ostensibly advising young men to avoid joining the armed services. Then, beginning in the 1930s, members were harassed for refusing to salute the flag and recite the pledge of allegiance. About the same time, they also began to experience pushback from their active evangelistic efforts such as distributing materials on the street and knocking on the front door of private residents. Their ability to practice and spread their faith would lead to multiple cases going to the Supreme Court for final resolution, most culminating in Witnesses prevailing. Their fight to defend their freedoms in the courts through the mid and late twentieth century expanded the understanding of the First Amendment freedoms to all American religions.